Job Condition of Women Laborers in Industrial Area: A Case Study of Balaju industrial Area, Kathmandu - Poudel, Tanka Mani (Gyanjyoti, 2023)
The paper explores the current situation of women labors in industry. It examines the women worker’s present job conditions in terms of job satisfaction, working hours and wages and their rights. This study was carried out on the Nebico Private Limited at Balaju Industrial Area. There were 65 labors working and I selected only 23 women by using the convenience sampling method as respondents of this study. The nature of the research approach was mix method. Moreover, the research employed both forms of data primary as well as secondary. In order to elicit the primary data, a face-to-face interview was conducted. The study reveals that women’s work is treated as unskilled labor and they face several other difficulties in comparison to males in their working space. It was found that more women labors were working in the factory for a longer period. In this study, out of 23 female respondents’ 39.13 percent are ethnically followed by Chhetri, 21.74 percent by dalits and 17.39 from Brahmin among total respondents. It was found that 43 percent of the women were working between one to three years of duration time period followed by one-third of them working less than years. Likewise, 22 percent of the women shared that they worked for three to five years of time duration. Women during her interview said that it was very difficult for them to find job and when they find a job it was more difficult to satisfy the person in their industry. However, they had no alternative than to continue their jobs.